Effect of Salinity Intrusion on Food Crops, Livestock, and Fish Species at Kalapara Coastal Belt in Bangladesh - Mohammad Zahangeer Alam; Lynne Carpenter-Boggs; Shishir Mitra; Md. Manjurul Haque; Joan Halsey; M. Rokonuzzaman; Badhan Saha; M. Moniruzzaman (Journal of Food Quality)
Salinity has caused significant negative effects on agricultural production. This research is focused on the vulnerabilities of soil and water salinities on crop, fish, and livestock production across the Kalapara coastal belt of Bangladesh. Several parameters were measured as indicators of salinity. The electrical conductivity of water was found to be significant with TDS, F−, Cl−, SO42-, Na+, K+, Ca2+, Mg2+, NO2-, and PO43-. Chloride was found to be identical with SO42-, Na+, K+, Ca2+, Mg2+, Br−, and PO43-. Electrical conductivity, F−, Cl−, SO42-, Na+, K+, and Mg2+ were all found to be higher than the recommended values. Similarly, soil conductivity was found significant with TDS, Cl−, SO42-, Na+, F−, NO2-, NO3-, and PO43-. Chloride in soil samples was found statistically identical with SO42-, Na+, NO3-, and PO43-. About 200 ha fodder crops areas are affected each year due to salinity. Ninety-two percent of the areas were found to be salinity affected in the 36 current cropping patterns. Twelve percent of marine fish and 25 percent of shrimp species have disappeared as a result of salinity. The negative impact of soil and water salinity on crops, fish, and livestock has been increasing in this coastal belt.